Bimbingan dan Konseling Islam dalam Meningkatkan Harga Diri Muallaf di Buleleng Bali - Winda Paramita, Winda Paramita; Saifullah, Saifullah (Fakultas Dakwah Universitas Ibrahimy, 2022)
Islamic guidance and counseling is the process of providing directed, continuous and systematic assistance to each individual so that he can develop his potential or religious na- ture optimally by internalizing the values contained in the Qur’an and Hadith. The purpose of this study was to determine the process of Islamic guidance and counseling in increasing the self-esteem of converts to Islam in Buleleng Bali. This study uses an action research met- hod using a cognitive approach. The results of the research that has been done regarding the process of Islamic Counseling Guidance to increase self-esteem in converts in Buleleng Ba- li, then: the counselee must think positively, make peace with the circumstances experien- ced, and read istigfar every day.